Caracterização do processo de assoreamento de reservatório urbano - MARIA EDUARDA ALVES FERREIRA (2020)
Locating the origin of sediments in urban environments becomes a challenge due to anthropogenic changes in the basin. The application of the sediment source tracking technique, called fingerprint, associated with the analysis of the basin's land use and bathymetric data, allows to quickly and economically identify the points in the basin that most contribute to the siltation of the reservoirs, helping in erosion reduction strategies processes and contain transported sediments. Among the factors that most affect the siltation of urban reservoirs are the interconnection with drainage, the mobilization and remobilization of sediments and the erosion of banks and stream beds.